Prevalence and Risk Factor of Unprotected Sex among HIV-infected Patients in Lower North: the Second Survey - ไชยมหาพฤกษ์, ศักดิ์ชัย (Disease Control Journal, 2018)
Thai Ministry of Public Health had implemented the program for training health care provider to provider sexual health service for PLWHA. This study was the second survey of sexual behavior of PLWHA, one year after training. The survey was conducted in 40 hospitals in five provinces in lower north between July 2009 and October 2009. There were 1644 PLWHA, the mean age was 38 years. 50°/o knew their HIV status after being ill then getting HIV testing. 53°/o believed that they got HIV infection from spouse. The unprotected sex during previous three-months period was 22°/o which was higher than the first survey conducted one year before. Unprotected sex in the hospitals where staffs attended the training program was lower than in the hospitals where staff did not attend but not statistically significant (22°/o vs 24°/o). Factors which decrease reported unprotected sex were disclosure of HIV status to sexual partner, male sex, under antiretroviral treatment. Divorced, widow reported higher unprotected sex than single. Prevention among PLWHA needed not only the training program, but policy and programmatic support with continuous monitoring and evaluation were essential. Early treatment with antiretroviral treatment, HIV status disclosure to sexual partner counseling, coupe voluntary counseling and testing, condom promotion and provision might reduce HIV transmission among intimate sexual partners which now was the majority proportion of new HIV-infected person in Thailand.